Critical Thinking Profile of Junior High School Class VIII Students in Solving the Pythagoras Theorem Problem in Review of Spatial Ability - Nurfadila, Nurfadila; Rochaminah, Sutji; Nurhayadi, Nurhayadi (Universitas Tadulako, 2020)
The purpose of this research is to obtain a description of the critical thinking profile of Junior High School Class VIII students in solving the Pythagoras theorem problem in review of spatial ability. This research uses qualitative methods based on the category of critical thinking according to Jacob and Sam. The results of research showed a critical thinking profile of high spatial ability subject (MC) on the categories: (1) Clarification, namely formulating problems and information accurately and clearly, as well as describing rectangles, (2) Assessment, namely choosing and using the formula of another subject, one right triangle to facilitate problem solving, (3) Inference, which is making precise and clear conclusions based on the information obtained, (4) Strategies, namely predicting answers using triple Pythagoras and proposing other alternatives by choosing other right triangle images and making another formula. The critical thinking profile of moderate spatial ability subject (BT) on the categories: (1) Clarification, namely formulating problems and information precisely and clearly, and describing the square, (2) Assessment, which is choosing a physical triangle elbows to facilitate problem solving, using other lesson formulas, but the formula used is not correct, (3) Inference, which is making inaccurate conclusions because it is not accurate, (4) strategies, namely evaluating solutions that are lacking right and have no other way of solving problems. The critical thinking profile of low spatial ability subject (AR) on the categories: (1) clarification, which is to formulate problems and information clearly but less precisely by writing and reciting the answer and no rectangular images known,(2) Assessment, which is choosing and using an inappropriate formula with inappropriate reasons, (3) Inference (inference), which is making inaccurate conclusions, (4) Strategies, namely unable to propose or predict or evaluate the answer and also have no other way of solving problems.